Coverage of the Noble Qualities of Zahiriddin Muhammad Bobur in the Lessons of History - Yuldash Haydarov (International Journal on Integrated Education, 2021)
In this article, the great statesman, skilled leader, great poet, scholar and architect Timurid prince Zahiriddin Muhammad Bobur who has noble human qualities as a faithful son, a loving father, a loyal friend, a loyal husband and a caring relative, and a just ruler are discussed in detail in the history lessons. Bobur's honoring of his elderly relatives, great attention to children's education and personality development, information is given about the use of vivid examples, such as advising his eldest son Humayun to learn the language perfectly and to pay attention to his speech and also to improve his personality.